A study to access the Impact of Magnesium Deficiency in the Obese Individuals - Durmaz, Zeynep Hülya; Demir, Aslihan Dilara; Demir, Orhan; Tiryaki, Meral (Eastern Journal of Medical Sciences, 2019)
Background: Obesity is an important health problem among developed and developing countries. Magnesium (Mg) deficiency is seen in obese individuals. Aim: To investigate the effect of Mg deficiency on insulin resistance in obese subjects. Methods: In this retrospective study, patients admitted to our hospital between 1 January 2016 and 31 December 2016 were included and data were retrieved from their medical records. We collected values of HbA1c, Mg, Glucose and Homa-IR and other biochemical tests. According to Body Mass Index (BMI), patients were divided into 3 groups. The relationship between Mg level and BMI was analyzed. Meanwhile, we also observed the relation between insulin resistance and BMI and relation between Hba1c and BMI. Results: A total of 134 patients, 21 male and 113 female, were included in the study. There was no statistical significance in serum Mg levels between the groups and there was a weak negative correlation between BMI and serum Mg levels. The correlation between BMI and insulin resistance was found to be moderately positive. On comparing, BMI and HbA1c between groups; it was statistically significant the groups consisting of BMIs below 25 and between 25-35, and the groups consisting of BMIs below 25 and >35. There was moderate positive correlation between BMIs and HbA1c levels. A negligible positive correlation between Mg levels and insulin resistance was observed. A weak negative correlation was found between Mg and HBA1C levels. Conclusion: Serum MG deficiency can be seen in obese individuals. Low serum Mg levels may accelerate the development of diabetes in obese individuals.